Functioning of Women with Migraine Headaches - Dorota Talarska; Małgorzata Zgorzalewicz-Stachowiak; Michał Michalak; Agrypina Czajkowska; Karolina Hudaś (The Scientific World Journal)
Background. Migraines are one of the most commonly occurring ailments affecting the nervous system. The aim of this research paper was to evaluate the effect migraines have on the everyday functioning of women. Method. The study involved women with diagnosed migraine headaches (IHS-2004) undergoing treatment at a neurological clinic. In order to evaluate the influence of headaches on the everyday functioning of women, a MSQ v.2 questionnaire was used, whereas pain severity was assessed on a linear VAS scale. Results. Among the clinical factors, the most influential was the frequency of headaches. Headache duration was particularly significant for women below the age of 40. Pain severity cited at 8–10 pts on the VAS significantly disrupted and limited everyday functioning. On the emotional function subscale, the most influential factors were age, education, and the frequency of headaches. Conclusions. On account of headache frequency emerging as the most significant influencing factor, it is of the utmost importance to inform patients of the value of taking prophylactic measures. Central to this is the identification of factors that trigger the onset of migraines. This approach would greatly aid the individual in choosing the appropriate treatment, either pharmacological or others.